Electrostatic Discharging Behaviour of Polycarbonate Parts Made by Process‐Integrated Surface Modification. Issue 11 (25th July 2014) - Nagel, Jürgen; Pahner, Felix‐Aron; Zimmerer, Cordelia; Härtig, Thomas; Gehde, Michael; Heinrich, Gert
<x xml:space="preserve">Abstract</x> The surface‐reactive injection moulding process is based on the reactive coupling between, e.g., a polyamine and polycarbonate (PC). The reaction takes place in a small layer and within a time of only about 1 μs before solidifying of the melt surface. Kinetic data are difficult to measure under those conditions. By model reactions in solution and in melt, first data on the reaction rate are available. Moulding experiments were made with a polyethylene imine (PEI), labelled with a naphthalimide dye. On injection of a PC melt, PEI layers of different thickness were transferred from the mould to the PC part surface. No significant residues remained on the mould surface. The thickness of the layer on PC was measured before and after solvent extraction. Conditions for best transfer and the maximum layer thickness are discussed. The electrostatic discharging behaviour of those layers on a PC part is shown.<inline-graphic xlink:href="ark:/27927/pgh2ck9dsvq" content-type="mame201400114-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />